Sustainability Concept In Developing Countries - Kulshreshtha, Surendra N. (IntechOpen, 2020)
Sustainability Concept in Developing Countries is a collection of seven studies addressing the issue of sustainability from the perspective of developing countries. Although it is not a comprehensive review of all developing countries, these contributions do portray some of the major issues in achieving sustainability in many developing countries. The book is divided into two parts: Part 1 includes chapters related to concepts and methodology relevant to sustainability in the context of developing countries. Part 2 presents some actual case studies including descriptions of the situations and advice on how to address sustainability in such economies. This book is a useful reference for professionals in developing countries as well as other jurisdictions.